STATISTICAL SIMULATION OF 2D RANDOM FIELD WITH CAUCHY CORRELATION FUNCTION IN THE GEOPHYSICS PROBLEM OF ENVIRONMENT MONITORING - Vyzhva, Z.; Demidov, V.; Vyzhva, A.; Fedorenko, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Due to the increasing number of natural and technogenic disasters the development of geological environment monitoring system is actual using modern mathematical tools and information technology. The local monitoring of potentially dangerous objects is an important part of the overall environment monitoring system. Complex geophysical research was conducted on Rivne NPP area. Among these monitoring observations radioisotope study of soil density and humidity near the perimeter of buildings is of the greatest interest. In this case a problem was occurred to supplement simulated data that were received at the control of chalky strata density changes at the research industrial area with use of radioisotope methods on a grid that included 29 wells. This problem was solved in this work by statistical simulation method that provides the ability to display values (random field on a plane) in any point of the monitoring area. The chalk strata average density at the industrial area was simulated using the built model and the involvement of the Cauchy type correlation function. This paper analyses the method and the model and procedure were developed with enough adequate data for Cauchy function. The method and algorithm were developed and examples of karst-suffusion phenomena statistical simulation were given in the problem of density chalk strata monitoring at the Rivne NPP area. The statistical model of average density chalk strata distribution was built in the plane and statistical simulation algorithm was developed using Cauchy function on the basis of spectral decomposition. The research subject realizations were obtained with required detail and regularity at the observation grid based on the developed software. Statistical analysis of the numerical simulation results was done and tested its adequacy.
Keywords: Statistical simulation; function Cauchy; spectral decomposition; conditional maps